PASTEURIZED HUMOBAVTER-A COMPOST AND SPRAYS OF LIQUID FERTILIZER TO SUPPRESS RHIZOCTONIAL DAMPING-OFF - HASSAN, WAZEER A.; DHAHIR, HEAVY M. (Journal of Duhok University, 2020)
Integrated management using organic peat – mix (Humobacter-A) plus NPK mineral fertilizer at 10, 20, and 30 mg kg-1 and spraying a full emergence seedlings with ALGIDEX; (organic liquid fertilizer plus extract of marine herb (Ascophilum nudosum) were applied for reducing the occurrence and severity of radish damping – off caused by Rhizoctonia solani Kuhn. NPK fertilization of incubated soil for 28 days reduced diseased seedlings to 27-35% and 23 - 37 % when used at 20 and 10 mg kg-1 respectively, prolonged incubation reduced disease occurrence to 27- 40 % when seedlings sprayed with 5 ml ALG. or by 20 mg NPK plus 20 ml ALG. Most of necrotic seedlings could be survived indicate that the compost and amendments suppressed post – emergence damping – off, since complete healthy seedlings were resulted when the soil incubated for 14 and 28 days and amended with 30 mg NPK kg-1 and 10 ml ALG. compared to 13.72 % and 7.84 % in the control. Heating of peat – mix at 50 0C for 5 days and incubated for 14 days suppressed the occurrence of damping – off to 27.45 % compared to 45 and 47 % when incubated for 28 and 7 days respectively. Necrotic seedlings restricted to only 5.88 % in the heated peat–mix incubated for 14 days with 20 ml ALG. Furthermore, disease severity reduced to the lowest rate (0.1) on seedlings grown in heated media under the same conditions. Thermophilic fungi of Aspergillus spp., Alternaria alternata, Humicola grisea, Penicillium spp. and Rhizopus stolonifer, was recovered incubated peat – mix for 28 or 14 days as 7.7 and 6.1 cfu g-1, respectively.